Drug-eluting stent for acute Blalock-Taussig shunt thrombosis in a child—case report - Arun Gopalakrishnan (The Egyptian Heart Journal, 2020)
Abstract Background Blalock-Taussig shunt (BTS) continues to have a relatively high operative and short-term mortality, even in the current era. We report the use of drug-eluting stent in a child with acute shunt thrombosis, which has not been reported in the literature to date. Case presentation A 7-month-old boy with double outlet right ventricle, severe pulmonary stenosis, and normally related great arteries underwent BTS placement for cyanotic spells. Ten days after discharge, he presented with shock due to a blocked BTS. He underwent emergency percutaneous revascularization of the shunt with a drug-eluting stent and is doing well at 9 months’ follow-up on dual antiplatelet therapy. Conclusions Drug-eluting stents may be used in children with BTS thrombosis.